Significant improvement in antibacterial property of ZIF-8 decorated graphene oxide by post-synthetic modification process - Ahmad, N. (Elsevier Ltd, 2021)
The effects of different ammonium hydroxide loadings towards morphological and antibacterial properties of ZGO composites in a straightforward post synthetic-modification were comprehensively investigated. Fourier Transform Infrared Spectroscopy (FTIR) result indicated a successful modification of ZGO with amine due to the existence of the NâH group, with minor changes in their crystal structure. Antibacterial activities were tested using Escherichia coli and Staphylococcus aureus as model strains of Gram-negative and Gram-positive bacteria, respectively, using disc diffusion (DDT) and minimum inhibitory concentration (MIC) test. The modified sample showed significant improvement against both bacteria. The best antibacterial activity was observed in ZGO-NH 20 with MIC values of 5 and 25 times lower than those of ZIF-8 and ZGO, respectively. Different mechanisms of bacterial death were proposed based on the FESEM images of the two bacteria after contact with the synthesized nanocomposites.The functionalization of ZGO with ammonium hydroxide significantly improved the antibacterial effect of the modified sample, depending on the loading volume of ammonium hydroxide used during modification. Overall, the synergistic effects of amine groups and metal zinc (Zn) in the ZGO-NH composites developed in this work may have tremendous potential as a beneficial antibacterial agent in the areas of water purification and biological applications. Â© 2021 Elsevier Ltd